2011
DOI: 10.1016/j.vaccine.2010.12.073
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T cell immunity to 2009 pandemic and seasonal H1N1 influenza viruses

Abstract: A novel strain of H1N1 influenza A virus (pH1N1) emerged in 2009, causing a worldwide pandemic. Several studies suggest that this virus is antigenically more closely related to human influenza viruses that circulated prior to 1957 than viruses of more recent seasonal influenza varieties. The extent to which individuals who are naïve to the 2009 pH1N1 virus carry cross-reactive CD8+ T cells is not known, but a certain degree of reactivity would be expected since there is substantial conservation among the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
25
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 56 publications
6
25
0
1
Order By: Relevance
“…Depending on the study and region analyzed, individuals under the age of 25 years represented 45% to 60% of infected subjects, though the pathogenic effects of H1N1 virus infection were most pronounced in individuals more than 60 years old (4,36). These findings, as well as recent immunological studies from our laboratory and other laboratories (11,17,20,22,25,33,39,48,51,52,55,61,62), suggest that previous encounters with vaccines or viruses provide immunological advantages and immunological memory in the population despite the "serological distance" between the hemagglutinin (HA) and neuraminidase (NA) proteins of seasonal and pandemic strains.…”
supporting
confidence: 58%
“…Depending on the study and region analyzed, individuals under the age of 25 years represented 45% to 60% of infected subjects, though the pathogenic effects of H1N1 virus infection were most pronounced in individuals more than 60 years old (4,36). These findings, as well as recent immunological studies from our laboratory and other laboratories (11,17,20,22,25,33,39,48,51,52,55,61,62), suggest that previous encounters with vaccines or viruses provide immunological advantages and immunological memory in the population despite the "serological distance" between the hemagglutinin (HA) and neuraminidase (NA) proteins of seasonal and pandemic strains.…”
supporting
confidence: 58%
“…The recent emergence of the 2009 pandemic influenza (H1N1) and avian influenza (H5N1) viruses has triggered a renewed interest in elements that confer immune protection across multiple strains of influenza virus. Multiple groups have reported that seasonal influenza vaccination can generate CD8 ϩ T cells that cross-react against pandemic and avian influenza virus antigens (26,34,38). In a mouse model, adoptive transfer of influenza virus H3N2-specific T cells can confer protection against the 2009 H1N1 influenza virus (17).…”
Section: Figmentioning
confidence: 99%
“…There is circumstantial evidence from human studies and animal models that T cells recognizing conserved epitopes can mediate heterotypic immunity against divergent influenza virus strains in the absence of crossreactive NAbs (15)(16)(17)(18)(19)(20)(21)(22), though this concept has so far been tested directly only in mice (21). Accordingly, a number of studies have suggested that infection with seasonal influenza virus provides a level of protection against the swine-origin pandemic 2009 influenza virus (H1N1pdm) in the absence of NAbs, an effect which may be mediated by cross-reactive T cell responses (17,(23)(24)(25)(26)(27)(28). However, the degree to which T cells can mediate effective, longlived heterotypic immunity to influenza in humans remains unclear.…”
mentioning
confidence: 99%